IMPLEMENTASI ISO 31000:2018 DALAM MANAJEMEN RISIKO FITUR GADAI PADA APLIKASI PEGADAIAN DIGITAL SERVICE - Aldo Jaya Mahendra; Evi Maria (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2024)
This research aims to apply the ISO 31000:2018 framework in risk management activities in the Pawn feature of the Pegadaian Digital Service (PDS) Application used at PT. UPC Mangunsarkoro pawn shop. PDS is a system that helps make it easier for customers to transact various pawnshop services online. This research data was obtained through interviews and observation. The stages of this research follow the ISO 31000:2018 standard, namely the communication and consultation stage, context setting stage, assessment stage, risk treatment, and monitoring and review stage. From the risk management activities in the Pawn feature of the PDS application, it was found that there were 11 risk opportunities in the application, with two risk opportunities at a high level, eight risk opportunities at a medium level, and one risk opportunity at a low level. The results of this research also provide suggestions for treating the risks in the Pawn feature of the PDS application and creating risk management documentation to help PT. Pegadaian UPC